Relationship among height, explosive power and shoulder strength on smashing accuracy in male badminton players - Asif, M.; Zutshi, K.; Munjal, J.; Dhingra, M. (European Journal of Physical Education and Sport Science, 2018)
Background: Badminton is one of the most popular racquet sports in the world. Into badminton, there are six basic strokes. Among these strokes, the most classical and powerful offending badminton technique used by the player to defeat the opponent is smashing. The Increase in height cans increments the number of positions in which an aggressive shot can be used. In badminton leg explosive power is a significant component and it results in the athlete being capable of moving instantly and constantly towards various directions of the shuttle and helping in lifting off the floor to play overhead strokes and Shoulder strength is a muscle`s capacity to bury the resistant to execute a shoot. So higher the shoulder strength greater the velocity of smash, also the strength of the stroke could affect its path. The smashing is quite dependent on height, explosive power and shoulder strength. The relationship between these predictors and criterion variable are highly related and should be analyzed. Objective: Find out Relationship among Height, Explosive Power and Shoulder Strength on Smashing Accuracy in Male Badminton Players. Methods: This was a correlational study. Total 60 athletes were selected for the study. Three main predictor variables were measured - Height was measured by Stadiometer, Explosive power was measured by vertical jump and shoulder strength was measured by overhead medicine ball throw. Criterion variable - smashing accuracy, was measured by taking six consecutive smashes on a marked badminton court. Result: Analysis of the data showed that height was statistically significantly correlated with smashing accuracy at a significant level, but explosive power and shoulder strength not significantly correlated.(p < 0.05) Conclusion: The findings of the study suggest that there exists a correlation between height and smashing accuracy in male Badminton players. Therefore, while selecting badminton players for the team during competitive events, Height would also be taken into consideration along with the sporting technique.